2014
DOI: 10.1021/pr5008703
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis of Exosome Protein Content Changes Induced by Hepatitis B Virus in Huh-7 Cells Using SILAC Labeling and LC–MS/MS

Abstract: Hepatitis B virus (HBV) infection could cause hepatitis, liver cirrhosis, and hepatocellular carcinoma. HBV-mediated pathogenesis is only partially understood, but X protein (HBx) reportedly possesses oncogenic potential. Exosomes are small membrane vesicles with diverse functions released by various cells including hepatocytes, and HBV harnesses cellular exosome biogenesis and export machineries for virion morphogenesis and secretion. Therefore, HBV infection might cause changes in exosome contents with funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 50 publications
0
51
0
1
Order By: Relevance
“…Flag or HA tags were introduced in some constructs to enable easier detection of expressed protein. Plasmid carrying terminally redundant 1.1X copy HBV genome downstream of CMV promoter with the HBx ORF nulled by introducing premature termination at residue 8 (1.1HBV-X − ) has been previously described10. CMV-driven eGFP expression plasmid (Beyotime) was used for transfection efficiency control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Flag or HA tags were introduced in some constructs to enable easier detection of expressed protein. Plasmid carrying terminally redundant 1.1X copy HBV genome downstream of CMV promoter with the HBx ORF nulled by introducing premature termination at residue 8 (1.1HBV-X − ) has been previously described10. CMV-driven eGFP expression plasmid (Beyotime) was used for transfection efficiency control.…”
Section: Methodsmentioning
confidence: 99%
“…Exosomes were prepared from cell culture supernatants using the classical method of differential centrifugation essentially as previously reported10. Briefly, supernatants were first centrifuged at 300  g for 10 min to remove detached cells and cell debris was removed by centrifugation at 2,000  g for 15 min followed by centrifugation at 10,000  g for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By applying an SILAC quantitative proteomics approach, Zhao and colleagues revealed that hepatitis B virus also alters the proteomic composition of hepatic cell line Huh-7-derived EVs [58]. A similar modulation was observed in the case of human T cell lymphotropic virus-infected T cell lines [59].…”
Section: Evs Secreted During Microbial Infectionmentioning
confidence: 75%
“…Negatively regulating the expression of exosomal miR-122In vitro studies of transfected cell lines HepG2 and Huh-7 cellSong et al [36]2. Significantly altering the exosomal protein contentIn vitro studies of transfected cell lines Huh-7 cellZhao et al [37] …”
Section: Introductionmentioning
confidence: 99%